Optical microscopy of fiber reinforced composites - Hayes, Brian S. (ASM International, 2010)
Optical microscopy is one of the most valuable--but under utilized--tools for analyzing fiber reinforced polymer matrix composites. This hands-on instructional book covers everything: sample preparation, microscopic techniques, and applications. The power of optical microscopy to study the microstructure of these heterogeneous, anisotropic materials is illustrated with over 180 full color images.
Keywords: Fibrous composites.; Microscopy.; Composite materials.; elektronické knihy; electronic books